Computational intelligence in music, sound, art and design : 7th International Conference, EvoMUSART 2018, Parma, Italy, April 4-6, 2018, Proceedings /: 7th International Conference, EvoMUSART 2018, Parma, Italy, April 4-6, 2018, Proceedings. (2018) - Unknown
No abstract available